Accent Interference Towards English Vowel Pronunciation Of Napunese EFLStudents - Kiko, Agri Satriani; Macora, Yuliana Dg. (Sintuwu Maroso Journal of English Teaching, 2024)
This study aims to find out the accent interference of Napunese students in pronouncing English vowels. The research was located in SMA Negeri 1 Lore Utara with 5 students of native Napunese speaker as the informants. The writers used recording of the pronunciation practice test and taking checklist as the instruments of data collection. In analyzing the data, the writers used Kelly’s theory (2000) about pure vowel sound, and supported by U-Dictionaries to crosscheck the correct pronunciation. From the findings obtained that the Napunese accent interference occur in all vowel sounds pronunciations produce by the Napunese students, for instance: in close vowel sound /i:/ is interfered by /e/, /ə/, /I/, /ea/ and diphthong /ei:/; vowel sound /I/ is interfered by /ə/, /e/, diphthong /eI/ and /aI/; vowel sound /ʊ/ is interfered by /u/ and /I/; vowel sound /u:/ is interfered by /Λ/ and /o/; for mid vowel sound /e/ is interfered by /I/ and diphthong /eI/; vowel sound /ə/ is interfered by /e/ and /Λ/; vowel sound /З:/ is interfered by /I/, and /o/; vowel sound /ɔ/ is interfered by /Λ/ and /o/; while for open vowel sound /æ/ is interfered by /e/, /Λ/, /ə/, /ɔ/ and diphthong /eI/; vowel sound /Λ/ is interfered by /o/ and /u/; vowel sound /α:/ is interfered by /o/ and diphthong /aI/, and vowel sound /ɒ/ is interfered by /Λ/ and /o/. The Napunese students of SMA Negeri 1 Lore Utara usually pronounced the English words similar to the written form, and sometimes they pronounced incompletely.